Ist das Zentrale-Orte-System als Raumordnungskonzept noch zeitgemäß? - Deiters, Jürgen (ERDKUNDE, 1996)
The hierarchical system of central places as an instrument for spatial development policy in the Federal Republic of Germany has largely lost its effectiveness. Nevertheless, the principle of central place arrangement has been accorded a special importance when setting up state and regional planning in the newly formed German states. Intended originally by the legislature as an instrument to develop backward regions, the German states had from the start set out a complete system of central places. Variability in settlement structure throughout Germany had been as contradictory to a uniform central place system as the varying selection principles used by the state authorities. The normative content of Christaller's central place model (importance of K-factors) has largely been neglected by the planning agencies; instead the received distribution of and provision for settlements is being elevated to the position of a planning goal. The concept of central places is too inflexible to shape the structural change of retail trade and services in a spatially compatible manner. Progressive centralisation of supply infrastructure in higher ranking centres has, for instance, led to gaps in supplies elsewhere, especially in sparsely populated rural areas, the closing of which requires solutions beyond the central place policies. The application of the central place system in spatial planning policy suffers from considerable weaknesses of the underlying theory. The basic postulates on spatial consumer behaviour (the nearest centre and the single-purpose shopping trip hypothesis, respectively) are as unrealistic as the corresponding assumptions about the behaviour of those offering central functions (monopolistic competition, dependent locational decisions). Fundamental to the understanding of agglomeration effects in central place systems and their dynamics of change today is the timing of demand (shopping frequency, not the range of central goods) in connection with the coupling advantage of multi-purpose trips. Moreover, market conditions in retail and customer services are marked by oligopolistic competition. The reformulation of the central place theory to provide a modern tool for explaining consumer spatial behaviour, the locational decisions of entrepreneurs, and the resulting hierarchical structure of centres and settlements as a new basis for central place policy, is not yet in sight. The following steps are suggested on spatial planning policy: as the concept of exhaustive central place systems exerts only a minor influence on settlement structure and regional development, it is to be dropped in favour of concentrating, on the one hand, on the protection of minimum provision in sparsely populated rural areas (as a social duty) with regionally-adjusted concepts and on the basis of improved behavioural theories, and on the other hand on opening-up a new and forward-looking area of responsibility by setting up urban networks of varying scales in order to increase decentralisation of regional and settlement structures in Germany; the basis for this could be the urban systems research which is based - among other things - on the hierarchical principle of central places.